2024
DOI: 10.1108/tr-11-2023-0816
|View full text |Cite
|
Sign up to set email alerts
|

Developing a thriving domestic tourism sector in emerging economies: a horizon 2050 paper

Elizabeth Agyeiwaah,
Bob McKercher

Abstract: Purpose The purpose of this paper is to argue for the development of a vibrant domestic tourism sector in emerging economies as a means of moving towards a more sustainable tourism sector and achieving many of the goals outlined in the UNWTO’s 2030 Agenda for Sustainable Development. Design/methodology/approach It uses a perspective approach through a critical state-of-the-art review of selected domestic and international tourism studies. Findings This paper illustrates how developing such a sector will pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The econometric research findings indicated a clear correlation between the growth of tourism and factors such as income per capita, trade openness, and the number of international visitors entering the country, these results are also consistent with Shan & Ren, 2023. After analyzing empirically, it was evident that there was a positive correlation between population and income per capita and CO2 emissions (Agyeiwaah & McKercher, 2024).…”
mentioning
confidence: 99%
“…The econometric research findings indicated a clear correlation between the growth of tourism and factors such as income per capita, trade openness, and the number of international visitors entering the country, these results are also consistent with Shan & Ren, 2023. After analyzing empirically, it was evident that there was a positive correlation between population and income per capita and CO2 emissions (Agyeiwaah & McKercher, 2024).…”
mentioning
confidence: 99%